Will political promotion expectation decrease the pay gap in state-owned enterprises in China?*. Issue 1 (2nd January 2016) - Bu, Danlu; Zhang, Chenyu; Lin, Teng
Abstract: In this paper, we test the effects of executives' promotion expectation on compensation and the pay gap between executives and employees in China. We measure the promotion expectation of current executives by using their predecessors' promotion ranks and direction. We find that there is a significantly negative relationship between promotion expectation and the pay gap, suggesting that senior executives with stronger expectation of political promotion are more willing to accept less compensation and therefore a smaller pay gap. Furthermore, we find that different types of promotion expectation have different effects on senior executives' perceptions. Compared with intra-group promotion, political promotion expectation has greater effects on limiting executive compensation and narrowing the pay gap. However, we find that promotion expectation fails to mitigate agency conflicts between shareholders and managers and further motivates the executives to maximise firm value.